Integrasi Seni dan Religi melalui Pelatihan Kaligrafi Kontemporer di Desa Mentoro - Fitri Umardiyah; Gigih Aziz Muslim; Farisy Maulana; Ummi Nailil Ulya; Khasanatun Na'imah; Ulfa Wulan Agustina; Novia Ayu Sekar Pertiwi; Hanifah Hanifah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Young people's interest in calligraphy tends to decline due to the dominance of modern digital visual culture, which is more practical and instantaneous. This has an impact on the suboptimal integration of artistic and religious values in community activities. The integration of art and religion can strengthen cultural identity while also serving as a contextual medium for preaching. The community service team conducted calligraphy training for TPQ teachers with the aim of increasing the interest of teachers and students in calligraphy. The target of this activity was TPQ teachers in Mentoro Village, Sumobito District. This training provided additional insight and skills to TPQ teachers in Mentoro Village regarding the art of calligraphy, while also fostering motivation to develop Islamic art in the educational environment. Despite limitations in time and resources, this activity still had a positive impact in terms of education, religion, and society. TPQ teachers showed great enthusiasm during the activity, so it is hoped that the knowledge gained can be passed on to students as a form of program continuity. Thus, this calligraphy training activity is the first step in strengthening the integration of art and religious values in Mentoro Village